The doctrine of benefit and burden: reforming the law of covenants and the numerus clausus “problem” - Bevan, Chris (Cambridge University Press, 2018)
The doctrine of benefit and burden - an indirect method for enforcing the burden of positive freehold covenants – developed as an exception the strict Austerberry rule that the burden of positive covenants cannot bind successors directly at law. Three recent Court of Appeal cases (Davies v Jones; Wilkinson v Kerdene and Elwood v Goodman) confirm the continued existence and application of the doctrine but also reveal its deficiencies and limitations. This article explores the contemporary application of the doctrine, identifies its theoretical, historical and elemental frailty and, drawing on recent reform proposals of the Law Commission, highlights the case for reform. In so doing, this article argues that a vital theoretical issue has been overlooked in the reform debate: the numerus clausus principle.